KOMODIFIKASI RAMADAN & COVID-19 DALAM IKLAN TELKOMSEL EDISI “TERUS JALANKAN KEBAIKAN” - Bayujati Prakoso; Khairul Syafuddin (Universitas Bina Sarana Informatika, 2020)
Nowadays, advertising is not merely having urgency as a means of promotion of commodities, but it has become the commodity itself that is worth selling to get a lot of financial profit. The concentration of advertisers turns into a commodity that sells (commodification). Advertising is a strategic pillar to be utilized by producers, including for producers of telecommunications service providers, Telkomsel. This research aims to uncover the significance of the commodification of Ramadan & Covid-19 in